PENGARUH CITRA MEREK, IKLAN DAN PERSEPSI KUALITAS TERHADAP NIAT BELI SEPEDA POLYGON DI BOJONEGORO - Dimas Bagus Rachmawan; Laila Saleh Marta (STIE Perbanas Surabaya, 2016)
This Globalization era led to the development of various field. One of the development is visible si the field of transport. One of the menas of transportused by the public at the time was a bike. Today the bike has been converted as a means of sport. For some young people often used as a hobby. The purpose of this research is to test and analyze the effect of Brand Image, Advertising and Perceived Quality for Purchase Intention Polygon Bike in Bojonegoro. Independent variable that supports this research is Brand Image, Advertising and Perceived Quality, mean while its dependent variable is Purchase Intention. The size of respondent in this research were 100 in Bojonegoro.Sampling technique used in this research is Judgement Sampling Technique Analysis used is multiple linear regression and using analysis tool of SPSS version 16.00. The result of this research is Brand Image, Advertising and Perceived Quality has significant and positive influence on Purchase Intention.